2021
DOI: 10.1038/s41467-021-21731-1
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 selectively regulates heat nociception and contributes to kinesin-mediated TRPM3 trafficking

Abstract: Effective treatments for patients suffering from heat hypersensitivity are lacking, mostly due to our limited understanding of the pathogenic mechanisms underlying this disorder. In the nervous system, activating transcription factor 4 (ATF4) is involved in the regulation of synaptic plasticity and memory formation. Here, we show that ATF4 plays an important role in heat nociception. Indeed, loss of ATF4 in mouse dorsal root ganglion (DRG) neurons selectively impairs heat sensitivity. Mechanistically, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…3F). Preclinical and clinical literatures support a positive association among up-regulation/activation of IL-6R (65-67), MEK (68-70), RUNX2 (71,72), FSH (73), and ATF4 (74,75) and nociceptive states, and several laboratories have validated interventions in relevant pathways as promising antinociceptive therapeutic strategies. Only AMPKα2 activity was expressed toward a pronociceptive direction in this list, because preclinical literature suggests that activation of this protein is associated with the alleviation of nociceptive symptoms (76,77).…”
Section: Drg Transcriptional Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…3F). Preclinical and clinical literatures support a positive association among up-regulation/activation of IL-6R (65-67), MEK (68-70), RUNX2 (71,72), FSH (73), and ATF4 (74,75) and nociceptive states, and several laboratories have validated interventions in relevant pathways as promising antinociceptive therapeutic strategies. Only AMPKα2 activity was expressed toward a pronociceptive direction in this list, because preclinical literature suggests that activation of this protein is associated with the alleviation of nociceptive symptoms (76,77).…”
Section: Drg Transcriptional Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…Nine URs met this criterion: Interleukin 6 Receptor (IL6R), Mitogen-activated Protein Kinase Kinase (MEK), Interleukin Enhancer-binding Factor 3 (ILF3), Runt-related Transcription Factor 2 (RUNX2), Protein Kinase AMP-Activated Catalytic Subunit Alpha 2 (PRKAA2) (UR was AMPKα2 gene), Follicle Stimulating Hormone (FSH), Activating Transcription Factor 4 (ATF4), Snail Family Transcriptional Repressor 1 (SNAI1), and Inhibin Subunit Alpha (INHA) ( Figure 3F ). Interestingly, pre-clinical and clinical literature supports a positive association between upregulation/activation of IL6R ( 6264 ), MEK ( 6567 ), RUNX2 ( 68, 69 ), FSH ( 70 ), & ATF4 ( 71, 72 ) and nociceptive states, and several laboratories have validated interventions in relevant pathways as promising anti-nociceptive therapeutic strategies. Only AMPKα2 activity was expressed towards a pro-nociceptive direction in this list, as pre-clinical literature suggests activation of this protein is associated with the alleviation of nociceptive symptoms ( 73, 74 ).These data suggest that other targets in this list may serve as novel therapeutic avenues of pain management.…”
Section: Resultsmentioning
confidence: 99%
“…A joint siRNA knockdown and knockout study indicated that ATF4‐deficient animals display reduced baseline, inflammatory, and neuropathic thermal sensitivities, yet fail to show changes in mechanical thresholds (M.‐X. Xie, Cao, et al, 2021 ). These results suggest that ATF4‐mediated transcription might affect transcripts involved in thermosensation, but not mechanosensation.…”
Section: Resultsmentioning
confidence: 99%